EFEKTIVITAS PEMBERIAN INFUSED WATER MENTIMUN DAN TERAPI AKUPRESUR PADA TITIK LI4 (HEGU) TERHADAP PENURUNAN HIPERTENSI PADA LANSIA DIWILAYAH KERJA PUSKESMAS KARANGTENGAH TAHUN 2022 - Pitriyani Pitriyani; Nurul Ainul Shifa (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Old age is one of the risk factors that affect hypertension because the higher the age, the higher the risk of getting hypertension, this is caused by natural changes in the body that affect blood vessels, hormones, heart. by using non-pharmacological treatment, namely the administration of cucumber infused water and acupressure therapy at the point of LI 4 (Hegu) can reduce blood pressure for people with hypertension. Purpose : This study aims to determine the effectiveness of cucumber infused water and acupressure therapy at the point of LI 4 (hegu) on reducing hypertension in the elderly. Methods: The population in this study was the elderly affected by hypertension with a total of 240 patients. In this study, the sample number was 30 respondents with each intervention group of 15 respondents. The type of this study is quantitative research that uses a two-group pretest-postest experimental model and is analyzed using statistical tests. Results: Based on the results of the study, it can be concluded that the results of the Wilcoxon test data there is an effectiveness between the administration of cucumber infused water and acupressure therapy at the LI4 (Hegu) point against reducing hypertension. With the results of v – palue 0.003 for the results of cucumber infused water against reducing hypertension and p-value 0.002 for the results of giving acupressure therapy at the LI4 point (Hegu) against reducing hypertension. In this study, there was a significant influence before and after intervention and blood pressure measurement was given in the working area of the Karangtengah Health Center. Conclusion : the effectiveness of cucumber infused water intervention and acupressure therapy at the LI4 (Hegu) point for the elderly affected by hypertension in the working area of the Karangtengah Health Center.